Endovascular reconstruction of bilateral upper limbs ischemia in a patient with arterial outlet syndrome: A case report and literature review - Zhou, Mi; Jia, Wei; Jiang, Peng; Cheng, Zhiyuan; Zhang, Yunxin; Liu, Jianlong (Frontiers in Surgery, 2022)
Background Acute upper limb ischemia in a patient with thoracic outlet syndrome is a rare but serious clinical disorder. If the disease is not treated promptly due to underdiagnosis, it could lead to distal artery embolization and limb-threatening ischemia. Revascularizing upper extremity arteries in a timely manner could rescue ischemic limbs and improve the patient’s quality of life. We reported here a case of a patient who presented with bilateral upper limb ischemia caused by arterial thoracic outlet syndrome. Case presentation A 63-year-old woman who presented with sudden bilateral upper extremity cold, numbness, pulselessness, and altered temperature sensation was first diagnosed with arterial thoracic outlet syndrome. The patient had performed a lot of pull-up and lat pull-down exercises in the 2 months prior to the onset of the above symptoms. Color Doppler ultrasonography showed thrombosis in the right axillary artery and left subclavian and axillary artery. The patient received Rotarex mechanical thrombectomy combined with drug-coated balloon percutaneous transluminal angioplasty (PTA) to complete revascularization of the upper extremities and achieved a full recovery finally. Conclusions Complete endovascular revascularization for treating arterial thoracic outlet syndrome is a minimally invasive and effective method, especially for upper extremity ischemic lesions caused by nonbone compression.